Half-red - McCarroll, Gracie, author; Cooperman, Matthew, advisor; Beachy-Quick, Dan, committee member; Lehene, Marius, committee member (Colorado State University. Libraries, 2015)
My process in writing this manuscript was much different that any process I had prior: I typed all the poems on a typewriter, made edits with a pen, then retyped them again and again on the typewriter. I didn’t touch the computer until I felt each draft was as close as possible to its highest pitch. I think this process allowed for a kind of fruition of the line that I had never before experienced. I hope for this manuscript to be a demonstration of the ways I have learned how to listen to my body, my ancestral echoes, my feet, and my poems. In line with Federico Garcia Lorca's conception of duende, I tried my hardest dismantle any intellectual scaffolding that began to appear in my poems. I wanted the poems to sing themselves into being. This involved radical tracking of each sound, word, and image. More specifically, I tried to see the first draft of the poem as containing all of the answers for revision. Words repeat; however, meanings never repeat themselves. This is something the Greeks knew in their conception of metis, meaning "beautiful arrangements." Arrangement activates words, strengthens their charges. Another hope for this work is that it eliminates the binary that seems to prevalent in academia between visual and literary arts. Writing my poems drove me to action. I believe that all art should drive the creator and audience into action. So I found myself meditating on Nick Cave's notion of art being capable of "creating a form for the spirit," and in doing so, I realized that poetry wasn't a large enough vessel to contain me or my grief. I stopped reading and thinking like writer. I started reading and thinking like a spirit. I bought two wedding dresses from Goodwill and began altering them with Cave's Soundsuits in mind. I started by sewing over 200 fake rose petals on each sleeve of one dress all by hand. This idea was prompted by Sappho's fragment "with arms like roses." I had in mind to create a dress that was the embodiment of romantic stage of a relationship. So I adorned the dress with fake ornaments until fabric started to rip. This was over a process that took about 6 months, as I did not own a sewing machine and the matter of using my hands to attach these objects seemed important for my body to understand the way the dress would function. For the second dress, I meditated on the disillusionment of a relationship and its dismantling. I sewed around a hundred glass test tubes from campus surplus store onto the wedding dress with fishing wire. This process took about 3 months. But to state the symbolic life of each dress is to belittle them and their potential. I am simply showing the evolution of my thought as concisely as possible. In truth, I did not know each dress would function as they did until I activated them but putting them on and videotaping myself. This activation made their function apparent as I began to let the ground and the dress move my body. I took many hours of video that I deleted, as I figured out you can just put something weird on and move around. You must craft gesture as you craft a line in a poem. My intention in the introduction is not to explain what the video work means to the manuscript or what the manuscript means to the video. I simply want to put them side by side and allow the audience to experience them (see my website http://www.graciemccarroll.com to watch the video; it is also important that you read the essay on the site that accompanies the video—the video and essay can be found under the "performance" tab; I very much want to video to be included in our defense conversation). I can only thank you all, from the sincerest part of my heart, for the faith, understanding, teaching and work you have done to help me become a better person, and therefore, a better artist. I hope you enjoy what follows.